2023
DOI: 10.2217/frd-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

GALILEO-1: A Phase I/II Safety and Efficacy Study of FLT201 Gene Therapy for Gaucher Disease Type 1

Abstract: Gaucher disease type 1 (GD1), caused by mutations in the GBA1 gene, results in β-glucocerebrosidase (GCase) deficiency. Gene therapy is under investigation as a potential treatment option for patients with GD1. The investigational gene therapy FLT201 consists of an adeno-associated virus (AAVS3) encoding a novel GCase variant (GCase-85). Preclinical characterization of FLT201 showed promising results, with GCase-85 being more stable at physiological pH than wild-type GCase and delivered effectively to target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The first (GALILEO-1), “A Gene Therapy Study in Patients with Gaucher Disease Type 1” (NCT05324943), conducted by Freeline Therapeutics, involves the administration of a liver-directed ssAAV to participants as a one-time intravenous infusion. The group made 37 GBA1 AAV constructs, which, when infused in mice with RC-04-26, resulted in the robust uptake of GCase by cells in spleen, bone marrow, and lung [ 98 ]. At this time, no results have been reported from the patient trial.…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…The first (GALILEO-1), “A Gene Therapy Study in Patients with Gaucher Disease Type 1” (NCT05324943), conducted by Freeline Therapeutics, involves the administration of a liver-directed ssAAV to participants as a one-time intravenous infusion. The group made 37 GBA1 AAV constructs, which, when infused in mice with RC-04-26, resulted in the robust uptake of GCase by cells in spleen, bone marrow, and lung [ 98 ]. At this time, no results have been reported from the patient trial.…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…While the stable expression in the nervous system is the most important factor for treating neuronopathic GD, it is also desirable to express GBA1 systemically to treat pathology in visceral organs [ 72 ]. Currently, there are a few active gene therapy clinical trials for the treatment of GD [ 73 ]. Miranda et al reported promising results regarding liver-directed gene therapy in vitro and in vivo for the treatment of GD.…”
Section: Treatment Of Lysosomal Diseases Regarding Liver Involvementmentioning
confidence: 99%
“…FLT201 is an experimental gene therapy that utilizes AAVS3 containing a unique variant of GCase (GCase-85). FLT201 has shown promising preclinical results, GCase-85 demonstrating improved stability at physiological pH as compared to wild-type GCase along with efficient transport to tissues targeted 12 .…”
mentioning
confidence: 99%